2014
DOI: 10.5888/pcd11.140329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alcohol Dependence Among US Adult Drinkers, 2009–2011

Abstract: IntroductionExcessive alcohol consumption is responsible for 88,000 deaths annually and cost the United States $223.5 billion in 2006. It is often assumed that most excessive drinkers are alcohol dependent. However, few studies have examined the prevalence of alcohol dependence among excessive drinkers. The objective of this study was to update prior estimates of the prevalence of alcohol dependence among US adult drinkers. MethodsData were analyzed from the 138,100 adults who responded to the National Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
235
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(247 citation statements)
references
References 15 publications
9
235
1
2
Order By: Relevance
“…Within the field of epidemiological research on drug dependence in cross-sectionally observed community samples, there is a tradition of plotting the number of days of drug use on the xaxis and the estimated probability of being drug dependent on the y-axis (Apelberg et al, 2014;Chen et al, 1997;Chen and Kandel, 2002;Esser et al, 2014). The result is a figure that resembles a dose-response or dose-effect curve from laboratory experiments designed so that dosage level or number of dosage days are "fixed effect" exogenous explanatory variables that are under the control of the experimenter.…”
Section: Introductionmentioning
confidence: 99%
“…Within the field of epidemiological research on drug dependence in cross-sectionally observed community samples, there is a tradition of plotting the number of days of drug use on the xaxis and the estimated probability of being drug dependent on the y-axis (Apelberg et al, 2014;Chen et al, 1997;Chen and Kandel, 2002;Esser et al, 2014). The result is a figure that resembles a dose-response or dose-effect curve from laboratory experiments designed so that dosage level or number of dosage days are "fixed effect" exogenous explanatory variables that are under the control of the experimenter.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to all alcohol-related problems, binge drinking is “responsible” for half of the 80,000 estimated deaths, two-thirds of the 2.3 million life years lost, and three-fourths of the $200+ billion economic costs annually. In addition to these hazards, binge drinking is concurrently related to prevalence of alcohol dependence at the population level (Esser et al, 2014), and, when measured in adolescence, has been predictive of later alcohol use disorders (AUDs; Jennison, 2004), and more generalized substance abuse diagnoses (Chassin, Pitts, & Prost, 2002). …”
mentioning
confidence: 99%
“…In fact, as few as 10% of binge drinkers meet criteria for alcohol dependence (Esser et al, 2014). In recognition of this disparity, the CDC has recommended physician screening and brief counseling for binge drinking (2014), and the United States Department of Health and Human Services (DHHS) has made reduction of binge drinking rates in young adults an objective in the Healthy People 2020 initiative (DHHS, 2011).…”
mentioning
confidence: 99%
“…[33] For binge drinking, BSI is most effective for non-alcohol dependent individuals, who comprise 90% of individuals who drink above recommended healthy limits. [58,59] For such individuals, brief interventions -ideally consisting of an initial 5-to 20-minute session plus one to three follow-up sessions -elicit reductions of 20% in days of binge drinking, 33% in injuries, 37% in hospitalizations 20% in emergency department visits and a $523 one-year reduction in net healthcare costs. [60] A study of disabled Medicaid emergency department patients found a $4,392 one-year net reduction in healthcare costs within one year.…”
Section: Outcomes Of Bsimentioning
confidence: 99%